Concomitant infection of Haemogregarina sp. and Staphylococcus aureus in free-living yellow-spotted river turtle (Podocnemis unifilis): case report. - Úngari, Letícia Pereira; Santos, André Luiz Quagliatto; Paiva, Guilherme Carrara Moreira; Mota, Kelem Cristina Pereira; Borges, Lizandra Ferreira de Almeida; Cury, Márcia Cristina (Archives of Veterinary Science, 2018)
A male adult yellow-spotted river turtle Podocnemis unifilis (Chordata: Testudines: Podocnemididae) was captured during field collections. Blood sample was collected for haemoparasite screening by conventional light microscopy. Morphometric and morphological analyzes of the parasite developmental stages were performed in the blood extensions, as well as the parasitemia intensity. Gametocytes of hemogregarines and innumerable bacterial cells were observed. To identify the bacteria present, a culture was performed and the presence of Staphylococcus aureus was observed. It was concluded that a co-infection of Staphylococcus aureus (Firmicutes: Bacillales: Staphylococcaceae) and Haemogregarina sp. (Apicomplexa: Adeleina: Haemogregarinidae) was observed in this free-living yellow-spotted river turtle Podocnemis unifilis.